2023
DOI: 10.1002/joa3.12895
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity C reactive protein levels and atrial fibrillation recurrence after catheter ablation for atrial fibrillation: A systematic review and meta‐analysis

Abstract: BackgroundAtrial fibrillation (AF) recurrence after AF ablation is not uncommon. High sensitivity C reactive protein (hs‐CRP) is a widely used inflammatory marker with a potential property to predict AF recurrence. We conducted a systematic review and a meta‐analysis to find an association between hs‐CRP levels and AF recurrence after ablation.MethodsWe searched PubMed, Embase, and Wiley‐Cochrane Library from inception to January 2022 for studies that reported hs‐CRP levels in patients who underwent AF ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…This observation might be indicative of higher baseline AF burden and higher inflammation in the AF recurrence group. However, a recently published meta-analysis reported that it was the post-ablation high-sensitivity CRP (hs-CRP) but not pre-ablation hs-CRP level that predicted AF recurrence [28]. The cause of inconsistency between our study and this meta-analysis regarding increased baseline CRP levels in patients with post-ablation recurrence is not clear, but the heterogeneity in patient characteristics might have contributed to the discrepancy.…”
Section: Discussioncontrasting
confidence: 76%
“…This observation might be indicative of higher baseline AF burden and higher inflammation in the AF recurrence group. However, a recently published meta-analysis reported that it was the post-ablation high-sensitivity CRP (hs-CRP) but not pre-ablation hs-CRP level that predicted AF recurrence [28]. The cause of inconsistency between our study and this meta-analysis regarding increased baseline CRP levels in patients with post-ablation recurrence is not clear, but the heterogeneity in patient characteristics might have contributed to the discrepancy.…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, hs-CRP emerges as a pivotal inflammatory factor intricately associated with inflammation and the development of AF. 2 Existing literature has proposed a cascade wherein inflammation triggers "atrial myocarditis," subsequently inducing electrical and structural changes in the atria, thereby initiating and perpetuating AF. 3 The measurement of acute-phase proteins, exemplified by hs-CRP, serves as a valuable window into a patient's prevailing inflammatory status.…”
Section: Clarifying the Association Between High-sensitivity C-reacti...mentioning
confidence: 99%
“…
The recurrence of atrial fibrillation (AF) remains an unresolved issue.Jaroonpipatkul and colleagues evaluated the association between high-sensitivity C-reactive protein (hs-CRP) and AF recurrence after catheter ablation. 1 The authors demonstrated that higher hs-CRP after ablation was associated with AF recurrence by performing a meta-analysis. Several concerns have been raised.Maintained sinus rhythm suppresses the inflammatory status.
…”
mentioning
confidence: 99%
“…One of the reasons why pre‐procedural hs‐CRP level was not associated with the AF recurrence in their study may be a variety of duration and burden of AF at baseline. 1 It may be more appropriate to perform a pooled analysis to prepare a more homogeneous cohort, instead of performing a meta‐analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation